The Effect of Prenatal Yoga on Maternal-Fetal Attachment Among Pregnant Women in the Third Trimester at The Sumidjah Blimbing Maternal and Child Health Clinic - Najah Rosyidah; Heny Astutik; Farida Halis DK; Ita Yuliani (Gayaku Publisher, 2026)
Background: Pregnant women in their third trimester often experience increased anxiety and emotional instability due to physical changes and concerns leading up to childbirth. These psychological conditions can hinder the mother's emotional connection with the fetus and reduce the quality of maternal-fetal attachment (MFA). Therefore, this study aims to determine the effect of prenatal yoga on maternal-fetal attachment in third-trimester pregnant women. Method: This study utilized an analytical observational design with a prospective approach. A total of 32 pregnant women in their third trimester were selected using consecutive sampling and divided into active and non-active prenatal yoga groups. Data were collected using the Maternal Fetal Attachment Scale (MFAS) questionnaire and analyzed using the Mann-Whitney U test. Result: In the active prenatal yoga group, nearly all participants (87.5%) demonstrated a high level of maternal-fetal attachment, whereas the majority of the non-active group (62.5%) showed a moderate level. Statistical analysis revealed a significant effect with a p-value of 0.001 (p < 0.05), indicating that prenatal yoga significantly affects maternal-fetal attachment in third-trimester pregnant women. Conclusion: Prenatal yoga effectively enhances maternal-fetal attachment in third-trimester pregnant women by increasing awareness of pregnancy changes, strengthening mother-fetus interaction, and providing relaxation and comfort. Consequently, prenatal yoga serves as a beneficial strategy to support the optimal development of the emotional bond between mother and fetus.